Ethiopian Economic Liberalization Policy Domains and International Competitive Priorities: Nexus of Export Performance of Manufacturing Firms After 1991 Economic Reforms - Mohammed Ahmed Endris; Abebe Ejigu Alemu; Abiyot Tsegaye Kiberet (World, 2025)
This study investigates the effect of Ethiopian economic liberalization policy and manufacturing firms’ international competitive priorities on the export performance after economic reforms in 1991. This study also aims to clarify how these economic reforms and the firm’s competitive priorities affect the international market export performance. This study further examines and identifies the most important variables that significantly affect export performance in relation to economic liberalization and the firm’s competitiveness. To achieve these objectives, both primary and secondary data were collected. A cross-sectional survey was conducted from 114 fully privatized manufacturing firms, utilizing a structured questionnaire with five Likert-scale items. The findings of this research indicate that law and order (LaO) and government intervention, incentive schemes, and trade openness have a significant relationship with the export performance of exporting firms in Ethiopia. This study also infers that firms must incorporate firm’s international competitive priorities’ cost, flexibility, and product quality as part of their competitive strategy. These competitive priority metrics limit export performance in terms of both subjective (e.g., export satisfaction) and quantitative (market share, profit) factors. This study concludes that economic liberalization and competitive priority measures are positive and have a significant relationship with the export performance of manufacturing firms in Ethiopia after 1991 reforms. The result also provides valuable insights for manufacturing firms and policymakers, highlighting the importance of economic liberalization in enhancing the export capabilities of privatized firms. These insights can guide the development of effective strategies to boost exports and foster sustainable economic growth.